2019
DOI: 10.1007/s13744-019-00681-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on the Genus Rhizoecus (Hemiptera: Rhizoecidae) with Description of Two New Species from South America

Abstract: Neotropical species of the scale insect genus Rhizoecus Künckel d’Herculais (Hemiptera: Coccomorpha: Rhizoecidae) found in soil sample material of the Hungarian Natural History Museum were studied. Two new Rhizoecus species, Rhizoecus kontschani Kaydan and Konczné Benedicty sp. n., and Rhizoecus granaradewillinkae Kaydan and Szita sp. n., are described and illustrated based on the adult females. Also, the adult females … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Hardiyanti et al [6] reported R. amorphophalli attack the porang tuber in India. They suck cell sap from the elephant foot yam tubers, and the severely infested deformed tubers find no place in market, nor are accepted for cooking [9,17,20].…”
Section: The Symptoms Of Mealybug Infested Porang Tubermentioning
confidence: 99%
“…Hardiyanti et al [6] reported R. amorphophalli attack the porang tuber in India. They suck cell sap from the elephant foot yam tubers, and the severely infested deformed tubers find no place in market, nor are accepted for cooking [9,17,20].…”
Section: The Symptoms Of Mealybug Infested Porang Tubermentioning
confidence: 99%
“…Most of the root mealybugs live in the soil, feeding on the roots of different plants but it is usually difficult to determine which plant is their actual host (Kaydan et al, 2019;Kozár & Konczné Benedicty, 2007). Rhizoecus albidus Goux, 1942, which is widely distributed in Europe and occurs also in Morocco, Kazakhstan and China as well as in the far eastern region of Russia (García Morales et al, 2016), is a new species to Polish fauna (Kalandyk-Kołodziejczyk, unpublished data).…”
Section: Introductionmentioning
confidence: 99%